Photovoltaic module simultaneous open-and short-circuit faults modeling and detection using the I-V characteristic (IEEE International Symposium on Industrial Electronics Jun , Buzios - Rio de Janeiro, Brazil, 2015)
This paper created a new research space in the faults modeling and detection area of the industrial systems, especially photovoltaic generators. It reserved for modeling and detection the hybrid defects, like the presence of cells open- and short-circuit within the same photovoltaic cells group. For a small investment, the new algorithm created a new platform. It exposed a display screen of the database, which presented the power of the PV module production in each period. The display screen allows real-time monitoring of the PV module production throughout the year, and detecting its anomalies.